Strategy Of Village Owned Enterprise in The Covid-19 Pandemic (Case Study at Koronua Village, Sabulakoa District, Konawe Selatan Regency) - Sunita Firdayana; Andi Asri; Ahsan Qasas; Rahmat Ibrahim; Caca Ardelia (International Journal of Management and Education in Human Development, 2022)
The main factor in the decline in business income of the village-owned enterprise when the establishment of BUMDes was not conducting a business feasibility analysis based on the village's potential (localization). Basically village-owned enterprise is based on community initiatives by looking at the potential of the village, but most villages establish BUMDes just to imitate other successful BUMDes. The purpose of the study was to obtain in-depth information about the strategy of village-owned enterprises in the COVID-19 pandemic by using a pattern of mutual cooperation, kinship, and mutual assistance in Koronua Village, Sablukoa District, South Konawe Regency. Using qualitative methods. The research was conducted from January 12 to February 20, 2022. This study analyzes the strategy of village-owned enterprises in the COVID-19 pandemic to survive a prolonged crisis. The strategy used with the pattern of gotong royong, kinship, and mutual care is the core strength of the people's economic pattern which tends to be traditional. This survival ability is only temporary, because the traditional pattern has the nature of surviving through a safe-seeking typology. This type of typology tends to be unproductive, so Village-Owned Enterprises (Bumdes) can only survive but cannot carry out faster and wider marketing expansion. The conclusion of the research is the discovery of strategies and innovations to strengthen Village Owned Enterprises as pillars of village communities in the context of village economic recovery. These strategies and innovations are in the form of actualization of mutual cooperation, kinship, and mutual care in the pattern of community economic development. It is recommended to apply practical economic activities and the practice of digitizing marketing in the community, so that economic growth moves to encourage post-pandemic revival.